Modelos de excelencia como ventaja competitiva: una revisión global (2016)
In the present research, it is determined by three objectives. The first of them applies and evaluates an integrated approach of the EFQM in relation to models of excellence at the global level. In order to develop the process of global management that integrates all levels, basic aspects that cover the design of a quality model. The second objective of this research describes the characteristics and advantages of quality systems seen as tools for the improvement of organizational management as a process of continuous improvement that tends towards customer orientation, increased cost efficiency, rapid action and flexible.